Analisis Kemampuan Representasi Matematis Ditinjau Dari Tingkat Kemampuan Siswa Dalam Penyelesaian Masalah Bentuk Aljabar Di SMPN 4 TanjungTahun Ajaran 2021/2022 - Rosfita Karolina; Laila Hayati; Junaidi Junaidi; Arjudin Arjudin (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to describe the ability of mathematical representation in solving algebraic problems in terms of the ability level of students at SMPN 4 Tanjung, the Academic Year 2021/2022. The type of research used is descriptive qualitative. The sample used was 27 students with the sampling technique used was purposive random sampling. Data collection techniques were carried out through tests and interviews. Based on the results of student test analysis, it was found that (1) the number of subjects in the high category was 6 students, indicating that the visual, symbolic, and verbal indicators were able to solve problems correctly and completely (2) the number of subjects in the medium category was 9 students. , shows that the visual, symbolic, and verbal indicators can state the problem but are incomplete (3) Furthermore, the number of subjects in the low category is 12 students, indicating that students have not been able to achieve the indicators of symbolic and verbal mathematical representation ability. The results of the research on students' mathematical representation abilities are 44.65%, the percentage value obtained from students' mathematical representation abilities on visual indicators is 18.31% in the high category, students' mathematical representation abilities on symbolic indicators are 15.43% in the medium category, then the ability students' mathematical representation of verbal indicators obtained 10.90% in the low category. This research on the ability of mathematical representation uses 3 indicators, namely visual or image representation, symbolic or expression, and verbal or written text words for further development by looking at other representational abilities.